2012
DOI: 10.4103/2249-4847.92234
|View full text |Cite
|
Sign up to set email alerts
|

Prune belly syndrome associated with full spectrum of VACTERL in a new born

Abstract: Prune belly syndrome (PBS) is a rare congenital anomaly of uncertain etiology. Many associations of PBS with other malformations were previously reported, but only few cases of the association with VACTERL have been described. We report a rare case of a Moroccan new born with PBS and complete VACTERL association. The cause of this association is still unknown, but a common etiology is possible, especially when for the two syndromes, a defect in mesodermal differentiation, in early first trimester, has been sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
(12 reference statements)
0
7
0
Order By: Relevance
“…The literature on aetiological and embryogenetic factors of PBS and PPBS is controversial. Some investigators postulate that the disease is due to three possible factors occurring during embryogenesis: severe bladder outlet obstruction, dysgenesis of yolk sac and possibly due to abdominal muscle deficiency secondary to a migrational defect of the lateral mesoblast between 6 th to 10 th weeks of pregnancy [ 1 , 3 , 4 ]. The chronic obstruction at the bladder neck is attributed to a dysplastic and dysfunctional posterior urethra [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature on aetiological and embryogenetic factors of PBS and PPBS is controversial. Some investigators postulate that the disease is due to three possible factors occurring during embryogenesis: severe bladder outlet obstruction, dysgenesis of yolk sac and possibly due to abdominal muscle deficiency secondary to a migrational defect of the lateral mesoblast between 6 th to 10 th weeks of pregnancy [ 1 , 3 , 4 ]. The chronic obstruction at the bladder neck is attributed to a dysplastic and dysfunctional posterior urethra [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Familial occurrence of the disease had suggested a genetic cause, but Granberg et al have shown that the implicated HNF1β mutation was detected only in 3% of patients with prune belly syndrome [ 6 ]. Associated anomalies are numerous and include those of the VACTERL group, gastrointestinal, orthopaedic and cardiopulmonary systems [ 1 , 3 , 4 , 7 ]. We presume that the aetiological and genetic factors and the associated anomalies in PBS and PPBS are similar, as these entities belong to a single group of congenital defects lying at both ends of a spectrum, and only differ in the severity of manifestations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prune belly syndrome (PBS) is a rare and usually a fatal congenital condition which presents with a partial or complete triad of deficient or absence of abdominal musculature, cryptorchidism and urinary tract anomalies [ 1 2 3 ]. Other congenital anomalies such as pulmonary hypoplasia, potters facies, clubfoot, imperforate anus are also found to be associated with PBS [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Genetically normal karyotyping is observed in most of the case of PBS [ 5 ]. However, Younous et al [ 3 ] and Metwalley et al [ 7 ] had reported PBS to be associated with Down's syndrome and other malformations like Vacteryl. Also, the chromosome 17q 12 deletions encompassing hepatocyte nuclear factor 1-β (HNF 1-β) can be determinate in cases of PBS [ 8 ].…”
Section: Introductionmentioning
confidence: 99%